2015
DOI: 10.4103/2226-8561.166369
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and academic uses of smartphones among medical residents

Abstract: Background and Objective: A smartphone is a cellular phone with an integrated computer that enables it to perform a wide array of tasks in addition to its primary purpose. Technological growth has been paralleled by a similar rise in the capabilities of modern day smartphones. And they have found their way into medical education as well as practice. iOS and Android based phones constitute the bulk of the smartphones. Together with their associated applications (apps), these devices have become an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…Based on a previous study conducted by Haseeb et al in Jammu, assuming a proportion of smartphone usage for academic learning among postgraduate students as 90% and taking absolute precision of 6% and a confidence interval of 95%, the estimated sample size was 96. The study subjects were recruited by convenience sampling method [ 6 ].…”
Section: Methodsmentioning
confidence: 99%
“…Based on a previous study conducted by Haseeb et al in Jammu, assuming a proportion of smartphone usage for academic learning among postgraduate students as 90% and taking absolute precision of 6% and a confidence interval of 95%, the estimated sample size was 96. The study subjects were recruited by convenience sampling method [ 6 ].…”
Section: Methodsmentioning
confidence: 99%
“…Based on the literature, most students believed that medical apps could restrain them from their education and acts as a hurdle to their academic pursuit (14). Also, medical students appeared uncertain about the superiority of medical apps to medical books (15). Another study reported that smartphones can act as a source of nuisance as depicted by most medical students because of frequent notifications of applications and more use of social networking apps, especially during study hours (16).…”
Section: Introductionmentioning
confidence: 99%